2003
DOI: 10.1103/physrevlett.90.132301
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy Photons from Passage of Jets through Quark-Gluon Plasma

Abstract: We calculate the production of high energy photons from Compton scattering and annihilation of a quark jet passing through a quark gluon plasma produced in a relativistic heavy ion collision. The contributions are large and reflect the momentum distribution of the jets and the initial conditions of the plasma.Relativistic heavy ion collisions are studied with the aim of producing a plasma of quarks and gluons (QGP). Photons are considered to be an important probe for the investigation of the formation and evol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
309
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(322 citation statements)
references
References 48 publications
12
309
1
Order By: Relevance
“…It does not reflect, however, the possibly large cancellation between the bremsstrahlung associated with hard jet production and the subsequent quark scattering, which was found to control induced gluon emission in finite nonAbelian plasmas [3,10,11]. Inverse Compton scattering in the QGP [12] has also been suggested as the dominant source of intermediate p T photons if the γ acquires most of the momentum of the incoming quark. Such enhancement effects, in conjunction with their associated negative azimuthal asymmetry coefficient v 2 (p T ) [8,13], do not appear to be compatible with existing direct photon data at RHIC [2,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not reflect, however, the possibly large cancellation between the bremsstrahlung associated with hard jet production and the subsequent quark scattering, which was found to control induced gluon emission in finite nonAbelian plasmas [3,10,11]. Inverse Compton scattering in the QGP [12] has also been suggested as the dominant source of intermediate p T photons if the γ acquires most of the momentum of the incoming quark. Such enhancement effects, in conjunction with their associated negative azimuthal asymmetry coefficient v 2 (p T ) [8,13], do not appear to be compatible with existing direct photon data at RHIC [2,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For such conversions, in Eq. (24) the p γ ≈ p c approximation [12] that stems from the limit of small tchannel momentum transfers to energetic jets is implicit. For a parent quark propagating through the QGP:…”
Section: Phenomenology Of Hard Photon Production In P+a and A+a Cmentioning
confidence: 99%
“…In 2002, we suggested that jets traveling through the plasma can radiate photons (and dileptons) as well and that this might be an important process [20,21]. The leading order channels for real photons are annihilation, q (jet)+q (medium) → γ + g and Compton scattering q (jet)+g (medium) → γ + q.…”
Section: Photons From Jetsmentioning
confidence: 99%
“…However, while evaluating jet-photon the authors in Ref. [2] assumes that the largest contribution to photons corresponds to p γ ∼ p q (pq). This implies that the annihilating quark (anti-quark) directly converts into a photon.…”
Section: Introductionmentioning
confidence: 99%
“…These apart, there exits another class of photon emission process via the jet conversion mechanism (jet-plasma * Electronic address: lusaka.bhattacharya@saha.ac.in † Electronic address: pradipk.roy@saha.ac.in interaction) [2] which occurs when a high energy jet interacts with the medium constituents via annihilation and Compton processes. It might be noted that this phenomenon (for Compton process) has been illustrated quite some time ago [3] in the context of estimating photons from equilibrating plasma.…”
Section: Introductionmentioning
confidence: 99%